Electrochemical Determination of Low Molecular Mass Thiols Content in Potatoes (Solanum tuberosum) Cultivated in the Presence of Various Sulphur Forms and Infected by Late Blight (Phytophora infestans) - Ryant, Pavel; Dolezelova, Eva; Fabrik, Ivo; Baloun, Jiri; Adam, Vojtech; Babula, Petr; Kizek, Rene (Sensors (Basel, Switzerland), 2008)
In the present paper potato plants were cultivated in the presence of ammonium sulphate or elemental sulphur supplementation into the soil to reveal the effects of different sulphur forms on content of nitrogen, phosphorus, potassium, calcium, magnesium and sulphur, and yield of tubers. During the investigation of the influence of different sulphur forms on yield of potato tubers we did not observe significant changes. Average weight of tubers of control plants per one experimental pot was 355 g. Application of sulphur in both forms resulted in moderate potato tubers weight reduction per one experimental pot compared to control group; average value ranged from 320 to 350 g per one experimental pot. Further we treated the plants with two different supplementation of sulphur with cadmium(II) ions (4 mg of cadmium(II) acetate per kilogram of the soil). The significantly lowest cadmium content (p < 0.05) was determined in tissues of plants treated with the highest dosage of elemental sulphur (0.64 mg Cd/kg) compared to control plants (0.82 mg Cd/kg). We also aimed our attention on the cadmium content in proteins, lipids or soluble carbohydrates and ash. Application of sulphate as well as elemental sulphur resulted in significant cadmium content reduction in lipid fraction compared to control plants. In addition to this we quantified content of low molecular mass thiols in potatoes tissues. To determine the thiols content we employed differential pulse voltammetry Brdicka reaction. After twelve days of the treatment enhancing of thiols level was observed in all experimental groups regardless to applied sulphur form and its concentration. Finally we evaluated the effect of sulphur supplementation on Phytophora infestans infection of potato plants.
Keywords: Cadmium; Potato (Solanum tuberosum); Differential pulse voltammetry Brdicka reaction; Late blight (Phytophora infestans); Glutathione; Electrochemical methods; Thiols; Heavy metal; Plant